2011
DOI: 10.1111/j.1540-8175.2011.01574.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Left Ventricular Dyssynchrony in Predicting Remodeling after ST Elevation Myocardial Infarction

Abstract: LV dyssynchrony is a strong predictor of LV remodeling after acute myocardial infarction (AMI). It could be useful in risk stratification of patients after AMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
14
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 30 publications
(74 reference statements)
2
14
0
1
Order By: Relevance
“…4 The frequency of LVr in our study was comparable to results recently published 10,18 in which investigators found that 22-33% of patients presented with remodeling within 6 months of an AMI treated with pPCI. LV remodeling post-AMI is an important precursor for the development of heart failure, and it is an important predictor of mortality.…”
Section: Discussionsupporting
confidence: 89%
“…4 The frequency of LVr in our study was comparable to results recently published 10,18 in which investigators found that 22-33% of patients presented with remodeling within 6 months of an AMI treated with pPCI. LV remodeling post-AMI is an important precursor for the development of heart failure, and it is an important predictor of mortality.…”
Section: Discussionsupporting
confidence: 89%
“…Cardiac dyssynchrony (DYS) is associated with functional deterioration and poor prognosis in advanced systolic heart failure and is an important determinant of postoperative outcome in patients with severe LV dysfunction . Furthermore, DYS is a strong predictor of LV remodeling after acute myocardial infarction …”
mentioning
confidence: 99%
“…5 Furthermore, DYS is a strong predictor of LV remodeling after acute myocardial infarction. 6 Two-dimensional (2D) strain imaging based on novel speckle-tracking echocardiography (STE) is a relatively new tool to define regional 1 The first two authors equally contributed to the article. myocardial strain and to quantify dyssynchrony based on a more robust technique and avoiding angle of incidence.…”
mentioning
confidence: 99%
“…Ventricular dyssynchrony is defined as loss of contraction coordination within or between ventricles and is thought to develop in failing heart. Abnormality of the timing of the events during cardiac cycle leads to pump inefficiency and energy expenditure . Dyssynchrony was first emphasized in the early studies in systolic HF patients with low EF and wide QRS complex, however, 1/3 of HF patients with a narrow QRS complex were found to exhibit substantial mechanical dyssynchrony as well .…”
Section: Discussionmentioning
confidence: 99%
“…Abnormality of the timing of the events during cardiac cycle leads to pump inefficiency and energy expenditure. 6,17 Dyssynchrony was first emphasized in the early studies in systolic HF patients with low EF and wide QRS complex, however, 1/3 of HF patients with a narrow QRS complex were found to exhibit substantial mechanical dyssynchrony as well. [18][19][20][21][22] Recently, systolic dyssynchrony was not only detected in the patients with symptoms of HF and preserved EF 7,23 but also in hypertension, diabetes mellitus, acute myocardial infarction, and hypo-and hyperthyroidism.…”
Section: Discussionmentioning
confidence: 99%